Traditional Chinese medicine for cardiovascular disease: efficacy and safety - Lin, Youwei; Han, Yuanshan; Wang, Yuhong (Frontiers in Cardiovascular Medicine, 2024)
In China and other Asian nations, traditional medicine has long been utilized in the treatment of cardiovascular diseases (CVD). While Chinese authorities have incorporated traditional Chinese medicine (TCM) treatment experiences as a supplementary guide for CVD, its international recognition remains limited due to a scarcity of high-quality and reliable randomized controlled trials (RCTs) evidence. The purpose of this study was to examine the clinical outcomes with TCM for CVD after the recent publication of large trials adding >20,000 individuals to the published data. Here, we systematically reviewed 55 published RCTs (modified Jadad scores > 4) in the past 20 years, involving a total of 36,261 patients. In most studies, TCM has been associated with significant improvements in alternative endpoints such as hypertension, coronary heart disease, stroke and heart failure. A total of 19 trials reported on primary outcomes such as cardiovascular events and death events. During the follow-up period, some Chinese patent medicines can effectively reduce the “hard” endpoints of coronary heart disease, stroke, and heart failure, the overall trend of cardiovascular outcomes is lower. The risk of adverse effects was not significantly increased compared to the control group, suggesting its potential as an alternative approach for primary and secondary prevention of CVD based on the available evidence.